Mouse chromosome-specific markers generated by PCR and their mapping through interspecific backcrosses. - Irving, N; Brown, S (1991)
We have utilized an oligonucleotide primer from the 3' end of the mouse L1 repeat element for amplification of mouse-specific inter-repeat PCR products from Chinese hamster/mouse somatic cell hybrids. PCR of a Chinese hamster/mouse somatic cell hybrid (96AZ2), containing only mouse chromosome 16, produced a range of mouse-specific bands. Two of the mouse-specific PCR products, of 250 and 580 bp, have been confirmed as originating from mouse chromosome 16 by somatic cell hybrid analysis. Both the 250- and 580-bp PCR products have been sequenced and demonstrate the expected sequence organization. Furthermore, both the 250- and 580-bp markers have been genetically mapped in detail to mouse chromosome 16 by direct hybridization to inter-repeat PCR products of progeny DNAs from Mus domesticus/Mus spretus interspecific backcrosses.